2018
DOI: 10.3897/subtbiol.25.23803
|View full text |Cite
|
Sign up to set email alerts
|

Is the Italian stream frog (Rana italica Dubois, 1987) an opportunistic exploiter of cave twilight zone?

Abstract: Studies on frogs exploiting subterranean environments are extremely scarce, as these Amphibians are usually considered accidental in these environments. However, according to recent studies, some anurans actively select subterranean environments on the basis of specific environmental features, and thus are able to inhabit these environments throughout the year. We present the first study on the abundance and spatial use of the Italian stream frog, Rana italica, in subterranean environments. We monthly collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The most obvious difference is the lack of light, a condition which not only contributes in reducing the fluctuation of the subterranean microclimatic conditions, but also impedes the colonization of plants, therefore strongly limiting the availability of Given the scarce quantitative ecological information on crane flies, our aim is to study the use of subterranean environments by these species and evaluate its potential relationships with cave-dwelling predators, as crane flies may represent an important food resource in an ecosystem characterized by constant scarcity [1]. Although, in the literature, only the presence of Limonia nubeculosa Meigen, 1804 is generally reported within Italian subterranean environments [30,39,47], the broad distribution of multiple species with similar habitus makes challenging their identification without manipulation [34,35]. Therefore, to avoid potential misidentification, we refer here to the whole superfamily Tipuloidea.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious difference is the lack of light, a condition which not only contributes in reducing the fluctuation of the subterranean microclimatic conditions, but also impedes the colonization of plants, therefore strongly limiting the availability of Given the scarce quantitative ecological information on crane flies, our aim is to study the use of subterranean environments by these species and evaluate its potential relationships with cave-dwelling predators, as crane flies may represent an important food resource in an ecosystem characterized by constant scarcity [1]. Although, in the literature, only the presence of Limonia nubeculosa Meigen, 1804 is generally reported within Italian subterranean environments [30,39,47], the broad distribution of multiple species with similar habitus makes challenging their identification without manipulation [34,35]. Therefore, to avoid potential misidentification, we refer here to the whole superfamily Tipuloidea.…”
Section: Introductionmentioning
confidence: 99%
“…We focused in assessing the major environmental features related to the occupancy of tipuloids within subterranean environments. Despite no specific adaptation toward the cave life, crane flies regularly frequent these environments [30,39], and previous studies suggested that ecological relationships with the cave environment can be extremely strong even for some species traditionally considered to be "accidental" [31,48]. Furthermore, we evaluated relationships between the distribution of crane flies and cave predators, as crane-flies can represent a major food resource in prey-deprived environments [30,43].…”
Section: Introductionmentioning
confidence: 99%
“…Trogloxenes are epigean species accidentally found in the shallowest part of subterranean environments. This classification, however, is viewed too strict ( Lunghi, Manenti & Ficetola, 2014 ; Romero, 2009 ), as species usually thought to be accidental are indeed potential residents playing an important role throughout the entire ecosystem ( Lunghi et al, 2018a ; Manenti, Lunghi & Ficetola, 2017 ; Manenti, Siesa & Ficetola, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, evidences have accumulated testifying that subterranean habitats are not entirely aseasonal Culver 1969, Tobin et al 2013), and that their inhabitants are not entirely arhythmic (Friedrich 2013, Abhilash et al 2017. Most subterranean habitats are indeed characterized by a constant flux of invaders and migrants (Chapman 1993, Culver and Sket 2002, Culver and Pipan 2009, Romero 2009, and there can be a temporal variability in the presence and distribution of vertebrates (e.g., Reichard et al 2009, Krofel 2010, Biswas 2014, Baker 2015, Ineich and Bourgoin 2016, Balogová et al 2017, Lunghi et al 2018) and invertebrates (e.g., Crouau-Roy et al 1992, Gnaspini et al 2003, Novak et al 2004, Papi and Pipan 2011, Tobin et al 2013, Mammola and Isaia 2014, Bento et al 2016, Mammola et al 2015, 2016a, Bichuette et al 2017, Lunghi et al 2017, Plăiaşu et al 2017 found in caves. For instance, invertebrates may move in search of food in larger cave chambers, and move back to the more stable fissures connected with caves in response to any physiological stress (Juberthie 1969, Chapman 1985.…”
Section: Introductionmentioning
confidence: 99%